Pengaruh Brand Ambassador Dan Digital Marketing Terhadap Keputusan Pembelian Di Tokopedia - Enrico Sasiang, Hizkia; Ali, Ahmad; Ruma, Zainal (Indonesian Journal of Research in Economy, 2022)
The purpose of this study was to determine the effect of Brand Ambassador and Digital Marketing on the purchasing decisions of management students at Tokopedia partially and simultaneously at the Faculty of Economics, Makassar State University. The type of research used in this research is quantitative research with a descriptive approach using multiple linear regression analysis method. The population in this study were active students of undergraduate management at the Faculty of Economics, Makassar State University, as many as 100 people and all of them were used as samples. The data collection technique used is by using a questionnaire (questionnaire). The results of this study indicate that partially Brand Ambassador has no influence on purchasing decisions, as evidenced by the tcount value of 0.335 which is smaller than ttable of 2.627 (0.035<2.627) and a significant value of 0.739 greater than 0.01 (0.739>0.01) , while Digital Marketing partially influences purchasing decisions as evidenced by the tcount value of 5.723, which is greater than the t-table value of 2.627 (5.723>2.627) and the significance value of 0.000 is smaller than 0.01 (0.00<0.01). Meanwhile, Brand Ambassador and Digital Marketing variables simultaneously influence purchasing decisions, this is evidenced by the statistical results Fcount of 20.388 which is greater than the value of Ftable 4.83 (20.388>4.83) and a significance value of 0.000 which is smaller than 0.01 (0.000<0.01).